"Concurrent Ropes and Ladders": Mapping and Conceptualizing the Emotional Loss Experience of Parents Following Pediatric Acquired Brain Injury. (July 2021) - Yehene, Einat; Steinberg, Pnina; Gerner, Maya; Brezner, Amichai; Landa, Jana
This grounded theory study aims to map, conceptualize, and theorize the emotional loss experienced by parents following their child's pediatric acquired brain injury (pABI). Data were obtained from 47 semi-structured interviews conducted with parents (72% mothers) at least 1 year following pABI. The study's theory of "concurrent ropes and ladders" emerged from a process of initial in vivo coding followed by focused and thematic coding. Codes were consolidated into five thematic categories capturing parents' emotional continuous loss experience: (a) comparing life before and after, (b) struggling to construct new realities, (c) recognizing instability and permanency, (d) adjusting and readjusting, and (e) grieving as an emotional shadow. These categories are at work simultaneously in parents' accounts, thus supporting a model of dynamic concurrency within and across their lived experiences. Recommendations for practitioners were derived from the theory to support parents' emotional coping with living loss throughout the chronic stage.